Human Granulocytic Ehrlichiosis Complicating Early Pregnancy. (30th April 2008) - Muffly, Tyler; McCormick, T. Chad; Cook, Christopher; Wall, Jeffrey
Abstract : Background . The goal of this case is to review the zoonotic infection, human granulocytic ehrlichiosis, presenting with pyrexia. Case . A 22-year-old multigravid female presented to the emergency department with a painful skin rash, high fever, and severe myalgias. The patient underwent a diagnostic evaluation for zoonotic infections due to her geographical and seasonal risk factors. Treatment of human granulocytic ehrlichiosis was successful though the patient spontaneously aborted presumably due to the severity of the acute illness. Conclusion . Treatment of human granulocytic ehrlichiosis in pregnancy presents unique challenges. Management of pyrexia during pregnancy is limited to external cooling in the setting of thrombocytopenia and elevated aminotransferases. Extensive counseling regarding teratogenic potential of medications allows the patient to weigh the pros and cons of treatment.